Evaluation of a mega-event facility: The case of the gremio's arena (ARQUISUR Revista, 2014)
The purpose of this article is to evaluate the impact generated by the Grêmio’s Arena, an equipment intended to host mega events, located at Farrapos village in Porto Alegre. Perceptions of residents of the area are analyzed regarding the visual impact of the Arena, the use of public spaces, the mobility in the neighborhood and the accessibility to other areas of the city. As methodological procedures, questionnaires were administered and interviews conducted with residents, plus observations of the uses of public open spaces in the study area. The data collected were tabulated in the software LimeSurvey and transferred to the software PASW Statistics 8 for analysis by non-parametric statistical tests. The main results show the positive aesthetic impact generated by the Grêmio’s Arena. Still, the intensity of use of public spaces by residents is directly related to the distance from such spaces to the Arena, evidencing a greater use of the streets and squares farther, especially on game days. The results allowed an advance in the knowledge about the impact of such equipments in residential urban areas, supporting the new insertions of this kind in an urban environment.
Keywords: grêmio’s arena; urban impact evaluation; equipment for mega events; environmental perception; urban spaces.